Violations of Rights of Children With Stunting in Indonesia - Suharso, Yohanes Leonard (Universitas Katolik Soegijapranata Semarang, 2023)
Abstract: Every child, including children with stunting, has the right to grow and develop. It has been stated in the Convention on the Rights of the Child and agreed upon by all participating countries, including Indonesia. The rights of children with stunting must be seen as the same rights as the rights of children who grow up healthily and optimally. Therefore, the state and parents are obliged to respect, protect, and fulfil the child’s rights. Community Health Centers (Pusat Kesehatan Masyarakat/Puskesmas), health service providers owned by the government, are responsible for realizing the rights of children with stunting. The problem found is that the prevalence of children with stunting in Indonesia in 2018 was 30.8% which is considered high (the WHO recommended prevalence limit is 20%). In addition, the lack of seriousness in stunting management also occurred in the work area of the Pegang Baru Community Health Center, Pasaman Regency, West Sumatra Province. Many stunting management programs are not carried out based on Standard Operational Procedure (SOP) which is considered only as a formality. In writing this conceptual article, a normative juridical approach was used by using secondary legal sources. The current state of stunting in Indonesia shows a violation of the right to grow and develop as well as the right to obtain proper health services for children with stunting by the state through the health centre as a functional unit.Abstrak: Setiap anak, termasuk anak stunting, mempunyai hak untuk tumbuh dan berkembang. Hal ini telah tertuang dalam Konvensi Hak Anak dan disepakati oleh seluruh negara peserta, termasuk Indonesia. Hak anak stunting harus dilihat sebagai hak yang sama dengan hak anak untuk tumbuh sehat dan optimal. Oleh karena itu, negara dan orang tua wajib menghormati, melindungi, dan memenuhi hak-hak anak. Pusat Kesehatan Masyarakat (Pusat Kesehatan Masyarakat/Puskesmas), penyedia layanan kesehatan milik pemerintah, bertanggung jawab untuk mewujudkan hak-hak anak stunting. Permasalahan yang ditemukan adalah prevalensi anak stunting di Indonesia pada tahun 2018 sebesar 30,8% tergolong tinggi (batas prevalensi yang direkomendasikan WHO adalah 20%). Selain itu, kurang seriusnya penanganan stunting juga terjadi di wilayah kerja Puskesmas Pegang Baru, Kabupaten Pasaman, Provinsi Sumatera Barat. Banyak program penanganan stunting yang tidak dilaksanakan berdasarkan Standar Operasional Prosedur (SOP) yang dianggap hanya sekedar formalitas. Dalam penulisan artikel konseptual ini digunakan pendekatan yuridis normatif dengan menggunakan sumber hukum sekunder. Kondisi stunting di Indonesia saat ini menunjukkan adanya pelanggaran terhadap hak tumbuh dan berkembang serta hak memperoleh pelayanan kesehatan yang layak bagi anak stunting yang dilakukan oleh negara melalui puskesmas sebagai unit fungsional.